New species and records of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from Bolivia - Arce-Pérez, Roberto; Morón, Miguel Ángel (Zootaxa, 2014)
Two new species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae) from Bolivia are described and illustrated: M. megaphyllus new species (from Comarapa, Santa Cruz and Sehuenca, Cochabamba) and M. yunganus new species (from Mairana and Comarapa, Santa Cruz). In addition, the species Macrodactylus bolivianus Moser, M. gracilis Moser, and M. nobilis Frey are redescribed and illustrated to help facilitate identification of these species. A key to the 10 species of Macrodactylus presently known from Bolivia is provided.